4 `-Epi-DNA: A DNA Mimic Containing 4 `-hydroxymethyl-alpha-l-Xylo-thymidine with compact backbone like RNA - Bagmare, Seema; Puranik, Vedavati G.; Fernandes, Moneesha; Kumar, Vaijayanti A. (Nucleosides Nucleotides & Nucleic Acids, 2016)
Synthesis of C4-epi-DNA containing 3 5 linkages is reported for the first time. Crystal structure study of the monomer indicated that though the dihedral angle O3-C3-C4-C5 in this case would be like in RNA, the sugar conformation would remain like that in DNA. The study of the effect of this backbone configuration in DNA with respect to its binding to cDNA and RNA is reported in this note.
Keywords: 4 `-hydroxymethyl nucleosides C4 `-epi-DNA; Antisense Oligonucleotide